2017
DOI: 10.1002/cbf.3266
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles–conjugated quercetin induces apoptosis via inhibition of EGFR/PI3K/Akt–mediated pathway in breast cancer cell lines (MCF‐7 and MDA‐MB‐231)

Abstract: Epidermal growth factor plays a major role in breast cancer cell proliferation, survival, and metastasis. Quercetin, a bioactive flavonoid, is shown to exhibit anticarcinogenic effects against various cancers including breast cancer. Hence, the present study was designed to evaluate the effects of gold nanoparticles-conjugated quercetin (AuNPs-Qu-5) in MCF-7 and MDA-MB-231 breast cancer cell lines. Borohydride reduced AuNPs were synthesized and conjugated with quercetin to yield AuNPs-Qu-5. Both were thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 64 publications
2
84
0
1
Order By: Relevance
“…We found that knockdown of WBP2 decreased the expression of EGFR, and key proteins involved in the EGFR/PI3K/Akt signaling pathway in TNBC cell lines. It is known that the EGFR/PI3K/Akt signaling pathway is the major cell survival pathway and plays an important role in cell growth, apoptosis, cell cycle progression, drug resistance, migration and invasion [27][28][29][30][31]. The EGFR signaling pathway has been reported to play an important role in the occurrence of TNBC, and the key proteins involved in this pathway may be effective therapeutic targets in TNBC [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…We found that knockdown of WBP2 decreased the expression of EGFR, and key proteins involved in the EGFR/PI3K/Akt signaling pathway in TNBC cell lines. It is known that the EGFR/PI3K/Akt signaling pathway is the major cell survival pathway and plays an important role in cell growth, apoptosis, cell cycle progression, drug resistance, migration and invasion [27][28][29][30][31]. The EGFR signaling pathway has been reported to play an important role in the occurrence of TNBC, and the key proteins involved in this pathway may be effective therapeutic targets in TNBC [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Also, myricetin, other flavonoid from flavonols subgroup, in ovarian, breast, prostate, and glioblastoma (Boam, ; Jiao & Zhang, ; G. Wang, Wang, Tang, Du, & Li, ; Xu et al, ), and butein, flavonoid from chalcones subgroup, in leukemia, pancreatic, cervical, lung, colorectal, and breast (Bai, Ma, & Zhang, ; Cho, Woo, & Ko, ; Chua et al, ; Y. T. Huang et al, ; Ishikawa, Senba, & Mori, ; S. K. Jung et al, ) have promising anticancer effects. Additionally, well‐known flavonoid quercetin, a plant flavonol, induced apoptosis in gastric, bladder, glioblastoma, breast, lung, colon, ovarian, cervical, liver, and pancreatic cancer cells (Balakrishnan et al, ; H. Li & Chen, ; Lin et al, ; Liu et al, ; Nwaeburu, Abukiwan, Zhao, & Herr, ; Raja et al, ; Ren et al, ; Roomi, Kalinovsky, Rath, & Niedzwiecki, ; Tao et al, ; E. X. Wang et al, ).…”
Section: Flavonoids: Cancer Therapymentioning
confidence: 99%
“…Several groups of investigators have shown that numerous genes such as RASSF1A, MLH1, BRCA1, WIF-1, CDH1, MGMT, and APC are hypermethylated and can be used as biomarkers or indicators of prognosis. 14 Epigenetic processes can be reversed and this principle makes it a potential target for therapeutic intervention. 15 Several studies demonstrate that silenced TSGs in cervical cancer cells are reactivated by the use of epigenetic inhibitors.…”
Section: Introductionmentioning
confidence: 99%